Avaliação das potencialidades do modelo de governança cobit no setor financeiro: case em uma empresa do sul do pais - Scariot, Ana Paula (Universidade do Vale do Rio dos Sinos, 2017)
For companies on the financial sector be strong in a competitive and regulated market, it would be necessary to offer a premium service, that satisfy the needs of customers. In front of it, it would be important that IT helps to create value, doing its activities align with the organization. This article objective is verifying how the IT operates related to the best practices of COBIT. The search was applied on a joint venture between a retail network and a bank, with some interviews to collaborators (CEO, managers and key users). After that, only five of those best practices are done on the organization, but no one has been managed. This five are: (i) ensure governance framework; (ii) ensure resource optimization; (iii) manage the IT Management Framework; (iv) management requirements definition; and (v) manage changes. On the interview, it was marked the needed of a better management and control of services, even before the governance, because IT is attending organization needs. For this reason, two proposes of improvement were suggested: a program to manage services and a program to control services/key performance indicators.
Keywords: Governança de TI; COBIT; Financeira; Tecnologia da informação; IT governance; COBIT; Financial institution; Information technology